2022
DOI: 10.1002/aenm.202200869
|View full text |Cite
|
Sign up to set email alerts
|

Improving Heat Transfer Enables Durable Perovskite Solar Cells

Abstract: Special attention should be devoted to the thermal stability of hybrid perovskite solar cells (PSCs), because they are often operated at elevated temperatures. However, effective strategies are lacking for manipulation of heat flow in PSCs to improve their thermal stability. Here, a holistic solution is reported for the rapid removal of dissipated heat within the absorber by introducing hexagonal boron nitride (h‐BN) inside and radiator fin outside of the device. This strategy significantly improves the therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
(62 reference statements)
1
20
0
Order By: Relevance
“…All the perovskite lms have diffraction peaks at 14.1°and 28.2°corresponding to the (001) and (002) planes of FAPbI 3 , which is consistent with previous research results. [29][30][31][32] This also indicates that the introduction of the CsPbI 3 QDs does not change the phase and crystal structure of the perovskite lms. The intensities of the (001) and (002) orientation peaks of the QD treated lm are higher than those of the control lm.…”
Section: Resultsmentioning
confidence: 99%
“…All the perovskite lms have diffraction peaks at 14.1°and 28.2°corresponding to the (001) and (002) planes of FAPbI 3 , which is consistent with previous research results. [29][30][31][32] This also indicates that the introduction of the CsPbI 3 QDs does not change the phase and crystal structure of the perovskite lms. The intensities of the (001) and (002) orientation peaks of the QD treated lm are higher than those of the control lm.…”
Section: Resultsmentioning
confidence: 99%
“…After heat treatment at 85 °C for 500 h, a large amount of PbI 2 appeared in the perovskite film with UV resin encapsulation (Fig. 2f), revealing that the heat accumulation might cause the loss of organic components and the decomposition of the perovskite 44 . As a comparison, few PbI 2 was observed at the surface of the perovskite film with target encapsulation after aging (Fig.…”
Section: Advantages Of the Target Encapsulation Strategymentioning
confidence: 99%
“…In addition, the thermal effect can be directly related to the initial efficiency of PSCs, because a large amount of evidences has confirmed that the effective thermal management could reduce the device temperature and thus raise the device efficiency. [ 12 ] For instance, Zhou et al reported an innovative method by introducing the silicon dioxide particles with highly thermal conductivity into the hole transport layer (HTL) to serve as the heat dissipation material. As a result, the resultant devices achieve substantially improved long‐term stability with the unencapsulated devices maintaining 91%, 95%, and 98% of their initial PCEs after 1126 h of thermal aging, 1235 h of SPO tracking, and 2000 h of ambient aging, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the thermal effect can be directly related to the initial efficiency of PSCs, because a large amount of evidences has confirmed that the effective thermal management could reduce the device temperature and thus raise the device efficiency. [12] For instance, Zhou et al reported an innovative method by introducing the silicon dioxide particles with highly thermal conductivity into the hole transport layer (HTL) to serve as the heat dissipation material. As a result, the resultant…”
mentioning
confidence: 99%